2021
DOI: 10.5433/1679-0359.2021v42n6supl2p3961
|View full text |Cite
|
Sign up to set email alerts
|

Beef cow weight variations during gestation and offspring performance: a meta-analysis

Abstract: The objective of this meta-analysis was to evaluate the effects of weight loss or weight gain of beef cows during the second and/or third trimester of gestation on the postnatal performance of the progeny. The variation in cow weight during the gestational period was calculated to standardize the treatments, being them: severe loss (SL = cows that lost more than 10% of weight); moderate loss (ML = cows that lost from 0 to 10% of weight) and weight gain (WG = cows that gained weight). The intensity of the cow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, the absence of fetal programming effects on progeny performance after birth may be a result of the adaptation and compensatory growth of calves to the growth environment, as well as the consequences of the "economic" phenotype generated in situations of nutritional stress during pregnancy (Mohrhauser et al, 2015). Complementing this hypothesis, Klein et al (2021b) found in a meta-analytic study that the effects of fetal programming are more noticeable in the early months of the progeny's life, with reflections, especially on the birth weight of the calves. Studying the severity of nutritional restriction in pregnant cows, Ramirez et al ( 2020) observed a greater recovery in weight gain from birth to slaughter in the progeny of severely restricted cows, when compared to calves from unrestricted or moderately restricted cows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the absence of fetal programming effects on progeny performance after birth may be a result of the adaptation and compensatory growth of calves to the growth environment, as well as the consequences of the "economic" phenotype generated in situations of nutritional stress during pregnancy (Mohrhauser et al, 2015). Complementing this hypothesis, Klein et al (2021b) found in a meta-analytic study that the effects of fetal programming are more noticeable in the early months of the progeny's life, with reflections, especially on the birth weight of the calves. Studying the severity of nutritional restriction in pregnant cows, Ramirez et al ( 2020) observed a greater recovery in weight gain from birth to slaughter in the progeny of severely restricted cows, when compared to calves from unrestricted or moderately restricted cows.…”
Section: Resultsmentioning
confidence: 99%
“…These changes in progeny performance can be permanent and can be observed in the adult life of the animal, although they are more noticeable in the initial months of the offspring's life (Klein et al, 2021b). In a meta-analytic study, Zago et al (2020) observed that the progeny of cows that consumed energy and protein above the maintenance requirements showed greater weight gain at finishing, were slaughtered 5.5 days earlier and presented meat with a higher marbling content, an aspect much appreciated by consumers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-weaning performance of males was similar between the nutritional levels of cows during the last third of pregnancy (Table 2). A meta-analytical study (19) demonstrated that the weight gain of the cow in pregnancy improves the performance of the progeny, and complements that these effects of the best maternal nutrition in the pregnancy are most evident in our initial two months of life.…”
Section: Male Performancementioning
confidence: 92%